Corporate risk management in Singapore's private residential property industry. - Chen, Xunru. (2008)
This research project focuses on the risks and exposures the Private Residential Property Development Industry faces and aims to provide useful insights to managers of property development firms on how they can effectively manage their risks and strengthen their position in the dynamic economy today.